Population pharmacokinetics and site of action exposures of veliparib with topotecan plus carboplatin in patients with haematological malignancies. (19th March 2017) - Mehrotra, Shailly; Gopalakrishnan, Mathangi; Gobburu, Jogarao; Greer, Jacqueline M.; Piekarz, Richard; Karp, Judith E.; Pratz, Keith; Rudek, Michelle A.
Abstract : Aims: Veliparib is a potent inhibitor of poly(ADP‐ribose) polymerase (PARP) enzyme. The objectives of the analysis were to evaluate the effect of baseline covariates and co‐administration of topotecan plus carboplatin (T + C) on pharmacokinetics of veliparib in patients with refractory acute leukaemia, and compare veliparib concentration in various biological matrices. Methods: A population pharmacokinetic model was developed and effect of age, body size indices, sex, creatinine clearance (CrCL) and co‐administration of T + C on the pharmacokinetics of veliparib were evaluated. The final model was qualified using bootstrap and quantitative predictive check. Linear regression was conducted to correlate concentrations of veliparib in various biological matrices. Results: A two compartment model with first‐order absorption with Tlag described veliparib pharmacokinetics. The apparent clearance (CL/F) and volume (Vc /F) were 16.5 l h −1 and 122.7 l, respectively. The concomitant administration of T + C was not found to affect veliparib CL/F. CrCL and lean body mass (LBM) were significant covariates on CL/F and Vc/F, respectively. While a strong positive relationship was observed between veliparib concentrations in plasma and bone marrow supernatant, no correlation was observed between plasma and peripheral blood or bone marrow blasts. Conclusions: Consistent with veliparib's physiochemical properties and its elimination mechanism, LBM and CrCL were found to affect pharmacokinetics of veliparib while concomitant administration of T + C did not affect veliparib's CL/F. Plasma concentrations were found to be a reasonable surrogate for veliparib concentrations in peripheral blood and bone marrow supernatant but not blasts. The current model will be utilized to conduct exposure‐response analysis to support dosing recommendations.